INKLUSI DIGITALISASI KEUANGAN UNTUK PENGUATAN TATA KELOLA BADAN USAHA MILIK DESA KUALA ALAM: STRATEGI PEMBERDAYAAN BERBASIS TEKNOLOGI - Zulpan Zulpan; Sutrisno Sutrisno; Sukron Niami; Zul Hendri; Sri Rahmany; Slamet Wiharto (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Digital transformation in the financial sector is an important aspect in strengthening the governance and performance of Village-Owned Enterprises (BUMDes). However, limited access and digital literacy are still major obstacles in the process, including in BUMDes Kuala Alam . This Community Service (PKM) activity aims to increase the inclusion of financial digitalization in BUMDes through training, mentoring, and adoption of digital application-based financial technology. The implementation method consists of identifying needs, training in digital financial systems, and evaluating the impact of implementation. The results of the activity showed an increase in the understanding and ability of BUMDes managers in using digital accounting and financial transaction systems. Recommendations from this activity include the need for the development of sustainable digital modules and integration with local financial institutions. Digital inclusion has been proven to strengthen the transparency and efficiency of village financial governance.